Ruling in turbulent times: government crises in Italy and Israel during the COVID-19 pandemic - Capati, Andrea; Improta, Marco; Lento, Tal (Frontiers in Political Science, 2023)
COVID-19 constitutes an unprecedented exogenous shock for democratic political systems across the globe. During this turbulent period, Italy and Israel have also experienced a government crisis. Building upon the “coalition life cycle” and the “critical events” approaches to government stability, this article explores the trajectories of the government crises in Italy and Israel in times of COVID-19. The article examines the impact of the cabinets' structural attributes and the pandemic in relation to the governments' early termination. In both countries, the oversized coalition configuration of the cabinets led to conflicts between the governing parties, which became untenable during the pandemic crisis, thus precipitating the governments' collapse.